A proton exchange membrane water electrolysis anode catalyst, preparation method and application thereof
By heat treatment on the carrier supported with elemental iridium, an oxide passivation layer is constructed and Ir oxidized, the problem of the supported catalyst being easily oxidized in depth and the elemental phase Ir being easily soluble under high oxidation potential is solved, and a high stability and activity proton exchange membrane water electrolytic anode catalyst is achieved.
Patent Information
- Application Number
- CN202310322748.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-03-29
AI Technical Summary
The supported catalysts used in the existing proton exchange membrane to produce hydrogen by electrolyzing water are prone to deep oxidation under high oxidation potential, resulting in a decrease in conductivity, and the elemental phase Ir is easily soluble in a strong oxidative and acidic environment, reducing the stability of the catalyst.
By heat treatment on the support supported with elemental iridium, a dense oxide passivation layer is constructed to prevent deep oxidation, while oxidizing elemental iridium to IrOx to maintain catalytic activity.
The stability and activity of the catalyst are improved, the amount of precious metal Ir is reduced, and the effects of low cost, high catalytic activity and good stability are achieved.
Smart Images

Figure CN116219491B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a proton exchange membrane water electrolysis anode catalyst, a preparation method and application thereof. Background Art
[0002] Proton exchange membrane water electrolysis (PEMWE) technology is one of the key technologies for producing green hydrogen from renewable energy. The highly oxidizing and acidic environment on the anode side places extremely high demands on oxygen evolution reaction (OER) catalysts. Currently, IrO2 has been found to be able to efficiently and stably catalyze acidic OER. However, the scarcity and high price of precious metal Ir resources severely limit the large-scale application of PEMWE technology. Therefore, it is imperative to develop low-Ir content catalysts with excellent IrO2-like performance.
[0003] In terms of catalyst design, the development of supported Ir-based catalysts is an effective strategy to reduce the amount of Ir in membrane electrodes, in which the carrier mainly plays the role of dispersing the active substance Ir. At present, a large number of studies are focused on screening carriers that can remain stable and have high electronic conductivity in the environment of the anode side of PEMWE. For example, materials with a certain conductivity, such as Ti and TiN, are used as carriers. However, these carriers are prone to uncontrollable deep oxidation under strong oxidizing conditions, and then transformed into oxides with extremely poor conductivity, resulting in the catalyst being unable to operate stably. Therefore, how to stabilize these carriers with high conductivity has become a challenging topic.
[0004] In addition, in order to obtain Ir nanocatalysts with smaller sizes on the support surface, polyol reduction or hydrogen reduction has become one of the best options, but the Ir on the surface of the supported catalyst obtained by this method is mainly a single phase. Compared with IrO2, single-phase Ir is more easily dissolved in a strong oxidizing and acidic environment, resulting in a decrease in catalyst stability. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a proton exchange membrane water electrolysis anode catalyst, a preparation method and application thereof, wherein the anode catalyst has excellent catalytic activity and stability.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a proton exchange membrane water electrolysis anode catalyst, comprising a carrier and IrOx and a passivation layer loaded on the carrier;
[0008] The carrier includes metal nitride, metal carbide, metal element and metal suboxide;
[0009] The passivation layer is an oxide formed by the metal in the carrier;
[0010] Among them, 1<x≤2.
[0011] Preferably, the metal nitride is selected from TiN and / or NbN.
[0012] Preferably, the metal carbide is selected from TiC and / or NbC.
[0013] Preferably, the metal element is selected from Ti and / or Nb.
[0014] Preferably, the metal suboxide is selected from Ti4O7 and / or NbO2.
[0015] Preferably, the passivation layer comprises TiO2 and / or Nb2O5.
[0016] Preferably, the mass ratio of IrOx to carrier is (0.1-4):1.
[0017] In a second aspect, the present invention provides a method for preparing the above-mentioned proton exchange membrane water electrolysis anode catalyst, comprising the following steps:
[0018] The supported catalyst loaded with elemental iridium is heat-treated at 100-900° C. to obtain an anode catalyst.
[0019] Preferably, the heat treatment is performed in an air atmosphere.
[0020] Preferably, the heat treatment time is 0.5 to 24 hours.
[0021] Preferably, the heating rate of the heat treatment is 0.2-10°C / min.
[0022] Preferably, the supported catalyst is prepared by a polyol reduction method or a hydrogen reduction method.
[0023] In a third aspect, the present invention provides an anode catalyst slurry for proton exchange membrane water electrolysis, comprising the anode catalyst, dispersant, binder and solvent involved in the above technical solution.
[0024] In a fourth aspect, the present invention provides a membrane electrode for proton exchange membrane water electrolysis, comprising an anode catalyst layer, a cathode catalyst layer, and a proton exchange membrane located between the anode catalyst layer and the cathode catalyst layer;
[0025] The anode catalyst layer is prepared by subjecting the anode catalyst slurry to a film-forming treatment.
[0026] In a fifth aspect, the present invention provides a sub-exchange membrane water electrolysis hydrogen production electrolytic cell, comprising the anode catalyst, anode catalyst slurry or membrane electrode involved in the above technical solution.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention heat treats the carrier loaded with elemental iridium, so that a dense oxide layer is constructed on the carrier surface as a passivation layer, which can effectively inhibit the uncontrollable deep oxidation of the carrier, thereby improving the overall operation stability of the catalyst. At the same time, the elemental iridium loaded on the surface of the carrier is oxidized to an IrOx phase with excellent activity, ensuring that the loaded low-Ir catalyst has IrO2-like performance. According to research, using this proton exchange membrane water electrolysis anode catalyst, the amount of precious metal Ir can be reduced to as low as 0.15 mg Ir cm -2 , while maintaining excellent activity and stability, with the advantages of low cost, high catalytic activity and good stability. In addition, the heat treatment process is simple, environmentally friendly, suitable for industrial large-scale production, and can reach several hundred grams, laying the foundation for the mass preparation of low-cost, high-activity, and long-life proton exchange membrane water electrolysis hydrogen production anode catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The polarization test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 1 and unoxidized Ir / Ti respectively;
[0030] Figure 2 The stability test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 1 and unoxidized Ir / Ti respectively;
[0031] Figure 3 The polarization test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 2 and unoxidized Ir / TiN respectively;
[0032] Figure 4 The stability test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 2 and unoxidized Ir / TiN respectively.
[0033] Figure 5 The polarization test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 3 and unoxidized Ir / Ti-H2 respectively;
[0034] Figure 6 The stability test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 3 and unoxidized Ir / Ti-H2 respectively;
[0035] Figure 7The polarization test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 4 and unoxidized Ir / NbN respectively;
[0036] Figure 8 The stability test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 4 and unoxidized Ir / NbN respectively;
[0037] Fig. 9 The polarization test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 5 and unoxidized Ir / TiC respectively;
[0038] Fig.10 The stability test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 5 and unoxidized Ir / TiC respectively;
[0039] Fig.11 The polarization test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 6 and unoxidized Ir / NbO2 respectively;
[0040] Fig.12 The stability test curve comparison diagram of the proton exchange membrane water electrolysis hydrogen production electrolytic cell assembled with the anode catalyst obtained in Example 6 and unoxidized Ir / NbO2 respectively. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] In view of the problem that the supported catalyst used for proton exchange membrane water electrolysis to produce hydrogen in the prior art is that the support is prone to uncontrollable deep oxidation at high oxidation potential, and is converted into an oxide with extremely poor conductivity, resulting in a decrease in the overall activity of the catalyst, and the single phase Ir in the catalyst is easily dissolved in a strong oxidizing and acidic environment, resulting in a decrease in the stability of the catalyst, the present invention provides a proton exchange membrane water electrolysis anode catalyst, including a support and IrOx and a passivation layer supported on the support, wherein the support includes metal nitrides, metal carbides, metal elements and metal suboxides; the passivation layer is an oxide formed after the corresponding metal in the support is oxidized; 1<x≤2. In some embodiments of the present invention, the metal nitride is selected from TiN and / or NbN, the metal carbide is selected from TiC and / or NbC, the metal element is selected from Ti and / or Nb, the metal suboxide is selected from Ti4O7 and / or NbO2, and the formed passivation layer includes TiO2 and / or Nb2O5. In the present invention, the higher the mass of the IrOx, the better the catalytic performance, but the cost will also increase accordingly. Therefore, in some embodiments of the present invention, the mass ratio of the IrOx to the carrier is preferably (0.1-4):1, specifically 0.1:1, 0.5:1, 1:1, 2:1, 3:1 or 4:1, etc. The ratios within the remaining ranges are also within the protection scope of the present invention and will not be repeated here.
[0043] The present invention heat treats the carrier loaded with elemental iridium, so that a dense oxide layer is constructed on the surface of the carrier as a passivation layer, which can effectively inhibit the uncontrollable deep oxidation of the carrier, thereby improving the overall operation stability of the catalyst. At the same time, the elemental iridium loaded on the surface of the carrier is oxidized to an IrOx phase with excellent activity, ensuring that the loaded low-Ir catalyst has IrO2-like performance. Using this proton exchange membrane water electrolysis anode catalyst, the amount of precious metal Ir can be reduced to as low as 0.15 mg Ir cm -2 , while maintaining excellent activity and stability, it has the advantages of low cost, high catalytic activity and good stability.
[0044] The present invention also provides a method for preparing the above-mentioned proton exchange membrane water electrolysis anode catalyst, comprising the following steps:
[0045] The supported catalyst loaded with elemental iridium is heat-treated at 100-900° C. to obtain an anode catalyst.
[0046] According to the present invention, the loaded catalyst loaded with elemental iridium can be prepared by a polyol reduction method or a hydrogen reduction method. The polyol reduction method and the hydrogen reduction method can be carried out according to methods well known to those skilled in the art. In some embodiments of the present invention, the polyol reduction method can refer to patent CN202110259388, and the hydrogen reduction method can refer to the document RSC Adv., 2017, 7, 31582-31587. In some embodiments of the present invention, the carrier of the loaded catalyst can be a material with high conductivity such as a metal nitride, a metal carbide, a metal element and a metal suboxide. The specific selection is as described in the relevant content of the above technical scheme, which will not be repeated here. In some embodiments of the present invention, the loaded catalyst obtained by the polyol reduction method or the hydrogen reduction method is preferably also dried, and the drying method can be any one of vacuum drying, freeze drying or forced air drying. The temperature of the vacuum drying or forced air drying is preferably 50 to 70 ° C, and the drying time is preferably 1 to 48 hours, more preferably 10 to 24 hours.
[0047] According to the present invention, after obtaining a dried supported catalyst loaded with elemental iridium, the supported catalyst loaded with elemental iridium is subjected to heat treatment at 100 to 900° C. to obtain the anode catalyst. In order to ensure that the powder sample is evenly heated and does not sinter during the heat treatment, in some embodiments of the present invention, the supported catalyst needs to be ground before the heat treatment, and the heat treatment is performed after the powder sample is evenly ground. During the heat treatment process, a heating rate that is too fast will cause the catalyst to be heated quickly and explode, and a heating rate that is too slow will cause the sample preparation cycle to be too long. Therefore, in some embodiments of the present invention, the heating rate is preferably controlled at 0.2 to 10°C / min, specifically 0.2°C / min, 0.5°C / min, 2°C / min, 4°C / min, 5°C / min, 6°C / min, 8°C / min or 10°C / min, etc., preferably 1 to 5°C / min, and the supported catalyst loaded with elemental iridium is heat-treated in an air atmosphere at 100 to 900°C, specifically 100°C, 200°C, 300°C, 400°C, 500°C, 600°C, 700°C, 800°C or 900°C, etc., preferably 200 to 700°C, more preferably 300 to 600°C for 0.5 to 24h, preferably 2 to 12h, more preferably 5 to 10h, and then cooled to obtain the anode catalyst. The cooling method can be natural cooling or quenching. In some embodiments of the present invention, the heat treatment is preferably performed in a muffle furnace.
[0048] The preparation method of the anode catalyst provided by the present invention is simple and easy to implement. The purpose can be achieved by simple heat treatment. It is environmentally friendly and suitable for large-scale industrial production. The mass of the product can reach several hundred grams, laying the foundation for the large-scale preparation of low-cost, high-activity and long-life proton exchange membrane water electrolysis hydrogen production anode catalyst.
[0049] The proton exchange membrane water electrolysis anode catalyst can be mixed with a dispersant, a binder and a solvent to prepare a proton exchange membrane water electrolysis anode catalyst slurry. The present invention has no particular restrictions on the dispersant, binder and solvent, and can be selected according to the conventional selection of those skilled in the art as needed. For example, the dispersant can be a non-ionic surfactant, specifically selected from polyethylene glycol octylphenyl ether; the binder can be selected from any one or more of perfluorosulfonic acid resin, polytetrafluoroethylene or polyvinylidene fluoride-hexafluoropropylene copolymer; the solvent can be selected from any one or more of isopropanol, ethanol, nitrogen-methyl pyrrolidone, nitrogen, nitrogen-dimethylformamide, dimethyl sulfoxide or glycerol.
[0050] The present invention also provides a membrane electrode for proton exchange membrane water electrolysis, comprising an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane located between the anode catalyst layer and the cathode catalyst layer. Wherein, the anode catalyst layer can be subjected to a film-forming treatment by the above-mentioned anode catalyst slurry, and can be prepared by ultrasonic spraying or scraping. The present invention has no particular restrictions on the cathode catalyst layer and the proton exchange membrane, and it can be a conventional choice for those skilled in the art. For example, the cathode catalyst layer can be obtained by ultrasonic spraying of a slurry including cathode catalyst Pt / C, and the proton exchange membrane can be selected from Nafion115 proton exchange membrane.
[0051] The present invention also provides a device for producing hydrogen by proton exchange membrane water electrolysis. The device may be a proton exchange membrane water electrolysis hydrogen production electrolysis cell, comprising the anode catalyst, anode catalyst slurry or membrane electrode involved in the above technical solution.
[0052] According to research, the use of heat-treated supported catalyst as the anode catalyst of the proton exchange membrane water electrolysis hydrogen production electrolysis cell can reduce the amount of precious metal Ir to 0.15 mg. Ir cm -2 , while maintaining excellent activity and stability, it has the advantages of low cost, high catalytic activity and good stability.
[0053] To further illustrate the present invention, the following examples are used to provide a detailed description. The experimental raw materials used in the following examples of the present invention can be purchased from the market or prepared according to conventional preparation methods known to those skilled in the art. The ethylene glycol reduction method described below can refer to patent CN202110259388; the impregnation loading and hydrogen reduction methods can refer to the literature RSC Adv., 2017, 7, 31582-31587.
[0054] Example 1
[0055] This embodiment provides an anode catalyst for producing hydrogen by proton exchange membrane water electrolysis, and the preparation method thereof is as follows:
[0056] At room temperature, hexamethyltrimethylammonium bromide was used as a surfactant and a supported catalyst (Ir / Ti) with Ti as the carrier was prepared by direct ethylene glycol reduction. The sample was placed in a 55°C vacuum oven and dried for 10 h, then taken out. After grinding evenly, 100 mg was weighed, placed in a quartz crucible, and placed in a muffle furnace for heat treatment at a heating rate of 5°C min -1 The target temperature is 500°C, the treatment time is 5h, and after naturally cooling to room temperature, the anode catalyst is obtained.
[0057] The anode catalyst obtained in Example 1 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its steady-state polarization curve is as follows: Figure 1 As shown in the figure, the prepared anode catalyst has a lower Ir loading and higher catalytic activity compared with the sample without heat treatment.
[0058] The anode catalyst obtained in Example 1 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its chronopotentiometric curve was as follows: Figure 2 As shown, compared with the sample without heat treatment, the prepared anode catalyst can operate stably for a longer time without obvious performance degradation.
[0059] Example 2
[0060] This embodiment provides an anode catalyst for producing hydrogen by proton exchange membrane water electrolysis, and the preparation method thereof is as follows:
[0061] At room temperature, polyvinyl pyrrolidone was used as a surfactant and a supported catalyst (Ir / TiN) with TiN as a carrier was prepared by direct ethylene glycol reduction. The sample was placed in a 55°C forced air oven and dried for 10 h, then taken out. After grinding evenly, 200 mg was weighed, placed in a quartz crucible, and placed in a muffle furnace for heat treatment at a heating rate of 8°C min -1 , the target temperature is 400℃, the treatment time is 5h, and after naturally cooling to room temperature, the anode catalyst is obtained.
[0062] The anode catalyst obtained in Example 2 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its steady-state polarization curve is as follows: Figure 3 As shown in the figure, the prepared anode catalyst has a lower Ir loading and higher catalytic activity compared with the sample without heat treatment.
[0063] The anode catalyst obtained in Example 2 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its chronopotentiometric curve was as follows: Figure 4 As shown, compared with the sample without heat treatment, the prepared anode catalyst can operate stably for a longer time without obvious performance degradation.
[0064] Example 3
[0065] This embodiment provides an anode catalyst for producing hydrogen by proton exchange membrane water electrolysis, and the preparation method thereof is as follows:
[0066] At room temperature, a supported catalyst (Ir / Ti) with Ti as the carrier was prepared by impregnation loading and hydrogen reduction. The sample was placed in a 55°C forced air oven and dried for 10 h, then taken out. After grinding evenly, 200 mg was weighed, placed in a quartz crucible, and placed in a muffle furnace for heat treatment at a heating rate of 4°C min -1 The target temperature is 600°C and the treatment time is 3h. After the treatment time is reached, it is immediately taken out and quenched to obtain the anode catalyst.
[0067] The anode catalyst obtained in Example 3 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its steady-state polarization curve is as follows: Figure 5 As shown in the figure, the prepared anode catalyst has a lower Ir loading and higher catalytic activity compared with the sample without heat treatment.
[0068] The anode catalyst obtained in Example 3 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its chronopotentiometric curve is as follows: Figure 6 As shown, compared with the sample without heat treatment, the prepared anode catalyst can operate stably for a longer time without obvious performance degradation.
[0069] Example 4
[0070] This embodiment provides an anode catalyst for producing hydrogen by proton exchange membrane water electrolysis, and the preparation method thereof is as follows:
[0071] At room temperature, hexamethyltrimethylammonium bromide was used as a surfactant and a supported catalyst (Ir / NbN) with NbN as the carrier was prepared by direct ethylene glycol reduction. The sample was placed in a 55°C forced air oven and dried for 10 h, then taken out. After grinding evenly, 200 mg was weighed, placed in a quartz crucible, and placed in a muffle furnace for heat treatment at a heating rate of 2°C min -1 The target temperature is 300°C and the treatment time is 3h. After the treatment time is reached, the temperature is naturally lowered to obtain the anode catalyst.
[0072] The anode catalyst obtained in Example 4 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its steady-state polarization curve is as follows: Figure 7 As shown in the figure, the prepared anode catalyst has a lower Ir loading and higher catalytic activity compared with the sample without heat treatment.
[0073] The anode catalyst obtained in Example 4 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its chronopotentiometric curve was as follows: Figure 8 As shown, compared with the sample without heat treatment, the prepared anode catalyst can operate stably for a longer time without obvious performance degradation.
[0074] Example 5
[0075] This embodiment provides an anode catalyst for producing hydrogen by proton exchange membrane water electrolysis, and the preparation method thereof is as follows:
[0076] At room temperature, hexamethyltrimethylammonium bromide was used as a surfactant and a supported catalyst (Ir / TiC) with TiC as the carrier was prepared by direct ethylene glycol reduction. The sample was placed in a 55°C forced air oven and dried for 10 h, then taken out. After grinding evenly, 200 mg was weighed, placed in a quartz crucible, and placed in a muffle furnace for heat treatment at a heating rate of 2°C min -1 The target temperature is 250°C and the treatment time is 5h. After the treatment time is reached, the temperature is naturally lowered to obtain the anode catalyst.
[0077] The anode catalyst obtained in Example 5 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its steady-state polarization curve is as follows: Fig. 9 As shown in the figure, the prepared anode catalyst has a lower Ir loading and higher catalytic activity compared with the sample without heat treatment.
[0078] The anode catalyst obtained in Example 5 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its chronopotentiometric curve was as follows: Fig.10 As shown, compared with the sample without heat treatment, the prepared anode catalyst can operate stably for a longer time without obvious performance degradation.
[0079] Example 6
[0080] This embodiment provides an anode catalyst for producing hydrogen by proton exchange membrane water electrolysis, and the preparation method thereof is as follows:
[0081] At room temperature, hexamethyltrimethylammonium bromide was used as a surfactant and a supported catalyst (Ir / NbO2) with NbO2 as a carrier was prepared by direct ethylene glycol reduction. The sample was placed in a 55°C forced air oven and dried for 10 hours, then taken out. After grinding evenly, 100 mg was weighed and placed in a quartz crucible, which was then placed in a muffle furnace for heat treatment at a heating rate of 2°C min -1 The target temperature is 300°C and the treatment time is 7h. After the treatment time is reached, the temperature is naturally lowered to obtain the anode catalyst.
[0082] The anode catalyst obtained in Example 6 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its steady-state polarization curve is as follows: Fig.11 As shown in the figure, the prepared anode catalyst has a lower Ir loading and higher catalytic activity compared with the sample without heat treatment.
[0083] The anode catalyst obtained in Example 6 was used to assemble a proton exchange membrane water electrolysis hydrogen production electrolytic cell, and its chronopotentiometric curve was as follows: Fig.12 As shown, compared with the sample without heat treatment, the prepared anode catalyst can operate stably for a longer time without obvious performance degradation.
[0084] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A proton exchange membrane water electrolysis anode catalyst, characterized in that: It includes a carrier, IrOx and a passivation layer loaded on the carrier; The carrier is a metal nitride, a metal carbide, a metal element or a metal suboxide; The passivation layer is an oxide formed by the metal in the carrier; Among them, 1<x≤2; The metal nitride is selected from TiN and / or NbN; The metal carbide is selected from TiC and / or NbC; The metal element is selected from Ti and / or Nb; The metal suboxide is selected from Ti4O7 and / or NbO2; The passivation layer is TiO2 and / or Nb2O5; The proton exchange membrane water electrolysis anode catalyst is prepared according to the following method: The supported catalyst loaded with elemental iridium is heat treated at 100-900°C.
2. The proton exchange membrane water electrolysis anode catalyst according to claim 1, characterized in that: The mass ratio of IrOx to the carrier is (0.1~4):
1.
3. The method for preparing a proton exchange membrane water electrolysis anode catalyst according to claim 1 or 2, characterized in that: The following steps are involved: The supported catalyst loaded with elemental iridium is heat treated at 100-900° C. to obtain an anode catalyst.
4. The preparation method according to claim 3, characterized in that: The heat treatment is carried out in an air atmosphere; The heat treatment time is 0.5 to 24 h; The heating rate of the heat treatment is 0.2~10 ºC / min.
5. The preparation method according to claim 3, characterized in that: The supported catalyst is prepared by a polyol reduction method or a hydrogen reduction method.
6. An anode catalyst slurry for proton exchange membrane water electrolysis, characterized in that: including anode catalyst, dispersant, binder and solvent; The anode catalyst is the anode catalyst according to claim 1 or 2, or the anode catalyst prepared by the preparation method according to any one of claims 3 to 5.
7. A membrane electrode for proton exchange membrane water electrolysis, characterized in that: It includes an anode catalyst layer, a cathode catalyst layer and a proton exchange membrane located between the anode catalyst layer and the cathode catalyst layer; The anode catalyst layer is prepared by subjecting the anode catalyst slurry according to claim 6 to a film-forming treatment.
8. A proton exchange membrane water electrolysis hydrogen production electrolytic cell, characterized in that: The invention comprises the anode catalyst according to claim 1 or 2, the anode catalyst prepared by the preparation method according to any one of claims 3 to 5, the anode catalyst slurry according to claim 6 or the membrane electrode according to claim 7.
Citation Information
Patent Citations
Corrosion-resistant metal oxide-based composite material as well as preparation method and application thereof
CN112973680A